A dual-channel noise reduction algorithm based on the coherence function and the bionic wavelet. (February 2018) - Nabi, Wahbi; Ben Nasr, Mohamed; Aloui, Noureddine; Cherif, Adnane
Abstract: A dual-microphone noise reduction method is proposed in this paper. It is based on the coherence function and the bionic wavelet transform using Kalman filter. This filter is applied to the Bionic wavelet coefficients obtained through the application of the BWT to the input signal. The adopted method can treat noisy signals using two closely spaced microphones in different noise scenarios and outperforms other dual-channel speech enhancement methods referring to the perceptual evaluation of speech quality, the spectrogram analysis and the time domain waveforms.